Faktor Determinan yang Memengaruhi Perilaku Swadiagnosis dan Swamedikasi pada Mahasiswa Kedokteran dan Non-Kedokteran - Lonah, Lonah; Halilintar, Via Dolorosa; Lauwly, Edlyn Edrea (Poltekkes Kemenkes Tanjung Karang, 2023)
Self-diagnosis and self-medication are some of the global health phenomena. Inappropriate behavior may lead to harmful effects such as misdiagnosis, antibiotic resistance, etc. Determinant factors such as age, gender, ownership of health insurance, and others are influencing self-medication. This study aims to find the prevalence of self-diagnosis and self-medication and the determinant factors influencing self-medication in university students. This study used a cross-sectional method conducted in April 2021 online. Using consecutive non-probability sampling, the research sample successfully obtained was 184 medical and non-medical faculty students. The research data were analyzed in univariate and bivariate. The prevalence of self-diagnosis and self-medication was 64.1% and 46.7% in the medical faculty-student group, then 63.0% and 43.5% in the non-medical faculty-student group. Duration of illness in the medical faculty-student group, self-diagnosis, and support from other persons in both groups of respondents significantly correlated with self-medication (p-value